Prevalence and 3‐year persistence of human papillomavirus serotypes in asymptomatic patients in Northern Mexico. Issue 1 (3rd November 2016) - Fajardo‐Ramírez, Oscar R.; Barboza‐Cerda, María C.; Ortiz‐López, Rocío; Rojas‐Martínez, Augusto; Garza‐Rodríguez, María L.; Sepúlveda‐Flores, Abel; González‐Guerrero, Juan F.; Bernal‐Silva, Sofía; Cerda‐Flores, Ricardo M.; Calleja‐Macías, Itzel E.; Rodríguez‐Flores, Socorro; Sandoval‐Guzmán, Esthela; et al.
Abstract: Objective: To investigate clinical outcomes and 3‐year persistence of human papillomavirus (HPV) infections among women in Mexico. Methods: A prospective study enrolled sexually active women attending primary healthcare clinics in metropolitan Monterrey, Mexico, between June 3 and August 30, 2002. Baseline data were collected and participants underwent HPV screening. Patients with HPV infections were asked to attend a repeat screening appointment after 3 years, when the same screening data were gathered. Descriptive analyses were performed and the prevalence of cervical lesions and viral infections were examined. Results: In total, 1188 patients who underwent initial HPV screening were included. Cervical lesions were detected in 5 (0.4%) patients and 239 (20.1%) patients had HPV infections; 129 (54.0%) of these patients attended 3‐year follow‐up. Among the 357 HPV serotypes identified, the most prevalent serotypes were HPV‐59, HPV‐52, HPV‐16, and HPV‐56, detected 62 (17.4%), 38 (10.6%), 27 (7.6%), and 18 (5.0%) times, respectively. Of the 129 patients attending 3‐year follow‐up, 104 (80.6%) were clear from HPV infections, 13 (10.1%) patients had persistent HPV infections, and 12 (9.3%) had HPV infections with different HPV types. Conclusions: The HPV prevalence was 20.1% in the present study; the most prevalent infections were HPV‐59, HPV‐52, HPV‐16, and HPV‐56. At 3‐year follow‐up, 25 (19.4%) patients had HPV infections. Abstract : HPV prevalence in Monterrey, Mexico, was 20.1%; the most prevalent form was HPV‐59. Of patients attending 3‐year follow‐up, 19.4% had continuing HPV infections.